Operation and Structure of Right-Wing Extremist Groups in the United States, 1980-2007 - Simi, Peter ([Verlag nicht ermittelbar], 2010)
The purpose of this study was to address some of the gaps in what is known about right-wing terrorism by (1) comparing right-wing extremist "advocates" with "implementers", and (2) identifying internal processes related to organizational planning and group roles by focusing on how right-wing extremist groups recruit new members. Using a wide variety of secondary sources, the principal investigator collected data beyond what was available in the AMERICAN TERRORISM STUDY, 1980-2002 (ICPSR 4639) and constructed an alternate database, the Right-Wing Terrorist Recruitment (RWTR) database, that related to terrorist recruitment and individual-level risk factors. The research team collected data on a total of 112 persons from 16 right-wing extremist (RWE) groups. In order to analyze the recruitment process, the principal investigator developed a new codebook that included a greater number of variables designed to measure different dimensions of the recruitment process. Some of the variables the investigator included were already in the American Terrorism Study dataset, however, the variable categories were revised. Other variables were included in light of prior terrorism studies and related scholarship such as research in the areas of social movements and new religious movements. The investigator also designed variables to measure the structural characteristics of the recruitment process. The dataset includes a total of 82 terrorist recruitment and individual-level risk factor variables.